ESG Commitment and Bank's Default Risk in Emerging and Developing Countries: Does Islamic Bank Matter? - Faaza Fakhrunnas; Turalay Kenc; Hengchao Zhang (Journal of Islamic Monetary Economics and Finance, 2025)
This paper examines the impact of ESG commitment on banks’ default risk in emerging and developing countries. Using a panel dataset comprising 157 banks from 28 countries over the period 2016-2022 and the Two-Step Generalized Method of Moments (2-Step GMM), it reveals that banks’ ESG commitment reduces banks’ probability of default (PD). Islamic banks also matter for ESG commitments, where Islamic banks have a higher probability of default than conventional banks while committing to the governance pillar. The findings of the study imply that financial authorities and banking institutions in emerging and developing countries need to spur banks’ ESG commitment. However, it must be carefully implemented in Islamic banks, considering that it likely increases Islamic banks' PD. The study contributes to the empirical research concerning the nexus between ESG commitment and banks' default by extending the measurement of the probability of default and delving deep into investigating its relation  to Islamic banks.